Effect of Market Waste Compost and Compound Fertilizer Application on The Vegetative Growth of Oil Palm Seedling (Elaeis guineensis Jacq) in Ultisol Growing Media - Ingrid Ovie Yosephine; Hardy Wijaya; Erwin Junaidi Lubis (The University of Lampung, 2022)
Compost is very important for the soil and is useful in increasing soil productivity and agricultural production in a sustainable manner where quality and quantity are achieved, as well reducing enviromental pollution and improving the quality of land (soil) in a sustainable manner. This study aims to determine the effect of chemical fertilizers and market waste compost addition on the vegetative growth of oil palm seedlings in the main nursery. The research was carried out for 8 months, from December 2019 - July 2020 in the area of the Practical Farm of the Field Laboratory of Soil Management, STIP-AP Medan. This study used a Randomized Block Design (RBD) with 2 factors. Factor 1 was organic compost made of market waste with 3 levels (0, 100, and 200 g/bag). Factor 2 was compound fertilizer (NPK 16:16:16) at 3 levels (5, 10, and 15 polybag). All treatment combinations wer performed in 3 replication plots and 2 seedlings were planted per plot, and 54 polybags in total. Data were analyzed using ANOVA at a level a = 5% and 1% and followed by Duncan's Multiple Range Test (DMRT) at a level a = 5%. The results prove that market waste compost and compound fertilizers had a significant effect on the observed parameters including plant height, number of leaves, and has a very significant effect on the parameters of fresh shoot weight and root fresh weight as well as shoot dry weight and root dry weight (g), but did not significantly affect the stem circumference. Keywords: compound fertilizer, main nursery, Market waste, oil palm, organic material